New species and records of the genus Paraphloeostiba Steel, 1960 (Coleoptera: Staphylinidae: Omaliinae) from Papua New Guinea, and notes on some species from India, Indonesia and Philippines - Shavrin, Alexey V. (Zootaxa, 2023)
New taxonomic and faunistic data for six species of Paraphloeostiba Steel, 1960 (Omaliini) from Papua New Guinea are provided. Five species are described or redescribed and illustrated: P. conjuncta sp.n., P. coriacea (Cameron, 1952), P. flaveola sp.n., P. papuana (Cameron, 1931), and P. ullrichi sp.n. (all from the Eastern Highlands of Papua New Guinea). The key for the species of Papua New Guinea is provided. The spermatheca of P. papuana is figured for the first time. New diagnostic and faunistic notes for four species from India, Indonesia and Philippines are presented. Several members of Paraphloeostiba are newly recorded: P. apicalis (Cameron, 1925) from India, P. subopaca (Cameron, 1924) from Tamil Nadu (India), and P. tonkinensis (Cameron, 1940) from Philippines (Leyte).